P154 Complexities in Tuberculosis care in seasonal farm workers in Scotland. (11th November 2022) - Ward, EM; Connell, DW; Allam, M; Ramsay, M; Chandler, D; Watson, D; Wilkie, M
Abstract : Introduction: Tuberculosis (TB) in the UK is still associated with significant morbidity, mortality and disproportionally affects migrants, and those in lower socio-economic groups. New entrant screening aims to identify those individuals with a higher risk of reactivation of TB upon entering the UK, but this may not be uniformly applicable. Methods: Within NHS Tayside, a mixed urban and rural area with high levels of deprivation, that serves approximately 7.6% of Scotland's population, TB incidence rates were estimated over 7 years to identify the groups with the highest TB incidence rates over time, and their disease phenotypes. Results: The three groups with the highest estimated incidence rates were Indian, Pakistani and Romanian with incidence rates respectively of 100, 130 and 140 per 100, 000; the incidence rate for Scottish born individuals was 5 per 100, 000. Moreover, and in contrast to other groups, rates of TB in Romanian nationals residing in Tayside were estimated to be around two times higher than the incidence rate of TB in Romania, presently estimated at 64/100000. All cases of TB in Romanian nationals over the last 7 years were pulmonary and included a child of 4 months suggesting recent transmission. Individuals from Romania treated for TB had a mean age of 33.5 y in comparison to 64 y for Scottish-born and 39 y for both Indian and Pakistani origin individuals. Only 37.5% of Romanian nationals completed treatment within Scotland. Discussion: Increased incidence and challenges of care of TB in persons from Romania within NHS Tayside is multifactorial and driven by specific needs of this largely seasonal farm-working group. Individuals from Romania are not subject to the pre-visa TB screening for those coming from countries with high incidence rates, nor included in new entrant screening within the UK. Individuals from these communities can experience intersectional difficulties in accessing healthcare, social help, and stable accommodation. Conclusions: TB in migrant workers is neither a new problem nor one isolated to NHS Tayside. Presenting the challenges faced here and developing solutions to these highlights that TB care in the UK at pre-elimination stages will need focused local, as well as national, solutions.